El Clima familiar y su correlación con el aprendizaje del idioma ingles de los estudiantes del quinto grado de secundaria de la Institución Educativa Ofelia Velásquez del año 2008 - Macedo Tuesta, Catherine (2009)
The following research has had the aim to know the correlation between family environment and English language learning among high school students of 5thyear from Ofelia Velasquez High School in Tarapoto city, 2008. Far this descriptive-correlative non-experimental study, a population of 264 students of 5th year from Ofelia Velasquez High School, who were registered in 2008 academic year, have been used and the Family Environment Scale (FES) has been applied to a sample of 157 students. The results of this study show us that there isn't any meaningful correlation between Relationship dimension and System Maintenance dimension of the family environment and English language learning; also we could find that there is a highly meaningful correlation in Personal Growth dimension and English language leaarning.